Systemic Infection by Non-albicans Candida Species Affects the Development of a Murine Model of Multiple Sclerosis - Fraga-Silva, Thais Fernanda de Campos [UNESP]; Munhoz-Alves, Natália [UNESP]; Mimura, Luiza Ayumi Nishiyama [UNESP]; Oliveira, Larissa Ragozo Cardoso de [UNESP]; Figueiredo-Godoi, Lívia Mara Alves [UNESP]; Garcia, Maíra Terra [UNESP]; Oliveira, Evelyn Silva [UNESP]; Ishikawa, Larissa Lumi Watanabe [UNESP]; Zorzella-Pezavento, Sofia Fernanda Gonçalves [UNESP]; Bonato, Vânia Luiza Deperon; Junqueira, Juliana Campos [UNESP]; Bagagli, Eduardo [UNESP]; et al. (MDPI, 2022)
Candidiasis may affect the central nervous system (CNS), and although Candida albicans is predominant, non-albicans Candida species can also be associated with CNS infections. Some studies have suggested that Candida infections could increase the odds of multiple sclerosis (MS) development. In this context, we investigated whether systemic infection by non-albicans Candida species would affect, clinically or immunologically, the severity of experimental autoimmune encephalomyelitis (EAE), which is an animal model used to study MS. For this, a strain of C. glabrata, C. krusei, and C. parapsilosis was selected and characterized using different in vitro and in vivo models. In these analysis, all the strains exhibited the ability to form biofilms, produce proteolytic enzymes, and cause systemic infections in Galleria mellonella, with C. glabrata being the most virulent species. Next, C57BL/6 mice were infected with strains of C. glabrata, C. krusei, or C. parapsilosis, and 3 days later were immunized with myelin oligodendrocyte glycoprotein to develop EAE. Mice from EAE groups previously infected with C. glabrata and C. krusei developed more severe and more prevalent paralysis, while mice from the EAE group infected with C. parapsilosis developed a disease comparable to non-infected EAE mice. Disease aggravation by C. glabrata and C. krusei strains was concomitant to increased IL-17 and IFN-γ production by splenic cells stimulated with fungi-derived antigens and with increased percentage of T lymphocytes and myeloid cells in the CNS. Analysis of interaction with BV-2 microglial cell line also revealed differences among these strains, in which C. krusei was the strongest activator of microglia concerning the expression of MHC II and CD40 and pro-inflammatory cytokine production. Altogether, these results indicated that the three non-albicans Candida strains were similarly able to reach the CNS but distinct in terms of their effect over EAE development. Whereas C. glabrata and C. Krusei aggravated the development of EAE, C. parapsilosis did not affect its severity. Disease worsening was partially associated to virulence factors in C. glabrata and to a strong activation of microglia in C. krusei infection. In conclusion, systemic infections by non-albicans Candida strains exerted influence on the experimental autoimmune encephalomyelitis in both immunological and clinical aspects, emphasizing their possible relevance in MS development.
Keywords: central nervous system; experimental autoimmune encephalomyelitis; Galleria mellonella; microglia; non-albicans Candida spp